Dolutegravir and pregnancy outcomes in women on antiretroviral therapy in Brazil: a retrospective national cohort study. Issue 1 (January 2021) - Pereira, Gerson Fernando Mendes; Kim, Ahra; Jalil, Emilia M; Fernandes Fonseca, Fernanda; Shepherd, Bryan E; Veloso, Valdilea G; Rick, Fernanda; Ribeiro, Rachel; Pimenta, Maria Cristina; Beber, Andrea; Corrêa, Renato Girade; Lima, Renato; et al.
Summary: Background: Dolutegravir has been widely available in Brazil since 2017. Following the signal that infants born to women with dolutegravir exposure at conception in Botswana had a higher risk of neural tube defects (NTDs), public health leaders initiated a national investigation to evaluate periconception dolutegravir exposure among all pregnant Brazilian women with HIV and its potential association with risk of NTDs, stillbirth, or miscarriage before 22 weeks (also called spontaneous abortion). Methods: In this retrospective, observational, national, cohort study, we identified all women with pregnancies and possible dolutegravir exposure within 8 weeks of estimated date of conception between Jan 1, 2017, and May 31, 2018, and approximately 3:1 matched pregnant women exposed to efavirenz between Jan 1, 2015, and May 31, 2018, using the Brazilian antiretroviral therapy database. We did detailed chart reviews for identified women. The primary outcomes were NTD and a composite measure of NTD, stillbirth, or miscarriage. NTD incidences were calculated with 95% CI. The composite outcome was examined with logistic regression using propensity score matching weights to balance confounders. Findings: Of 1427 included women, 382 were exposed to dolutegravir within 8 weeks of estimated date of conception. During pregnancy, 183 (48%) of 382 dolutegravir-exposed and 465 (44%) of 1045 efavirenz-exposed women received folic acid supplementation. There were 1452 birth outcomes. There were no NTDs in either dolutegravir-exposed (0, 95% CI 0–0·0010) or efavirenz-exposed groups (0, 95% CI 0–0·0036). There were 23 (6%) stillbirths or miscarriages in 384 dolutegravir-exposed fetuses and 28 (3%) in the 1068 efavirenz-exposed fetuses (p=0·0037). Logistic regression models did not consistently indicate an association between dolutegravir exposure and risk of stillbirths or miscarriages. After study closure, two confirmed NTD outcomes in fetuses with periconception dolutegravir exposure were reported to public health officials. An updated estimate of NTD incidence incorporating these cases and the estimated number of additional dolutegravir-exposed pregnancies between Jan 1, 2015 and Feb 28, 2019, is 0·0018 (95% CI 0·0005–0·0067). Interpretation: Neither dolutegravir nor efavirenz exposure was associated with NTDs in our national cohort; incidence of NTDs is probably well under 1% in dolutegravir-exposed HIV-positive women but still slightly above HIV-uninfected women (0·06%) in Brazil. Funding: The Brazilian Ministry of Health and the United States' National Institutes of Health.